The use of ambon banana (Musa paradisiaca var. sapientum) stems flour in grouper (Epinephelus lanceolatus ♂× Epinephelus fuscoguttatus ♀) floating net cage nursery - Wahjuningrum, Dinamella; Lestari, Diah Ayu; Mulyadin, Aldy; Effendi, Irzal (Jurnal Akuakultur Indonesia, 2022)
The study aimed to test the effectiveness of ambon banana stems flour through feeding on the health status and performance of the groupers reared in the sea floating net cages. The groupers (8.27 ± 0.20 cm length and 11.69 ± 0.50 g weight) were reared in 1 m × 1 m × 1.5 m floating net cages with a stocking density of 112 fish /m3 for 42 days. The feed was commercial feed with 46% and 48% protein, which was added with 30 g/kg of ambon banana stems flour with a coating method. This study consists of three treatments and three replications, i.e. feeding at the beginning of reared for 7 days (A), 14 days (B), and feeding without ambon banana stems flour (control). The observed parameters were production performance, morphometric, hematological test, and water quality. The results showed that the production performance between treatments was not significantly different (P>0.05). Based on the morphometric test the total length for treatment A increased significantly (P <0.05) compared to the control and B. On the 14th day of the hematological test, it was known that the highest total erythrocyte, hemoglobin, hematocrit, and total leukocyte was found in treatment B, however, the differential leukocyte did not differ significantly (P>0.05). The addition of Ambon banana stems flour in feed in the first 14 days (B) can improve health status but has not been able to increase production performance and morphometric grouper. Keywords: cantang grouper fish, production performance, health status, Ambon banana stems flour ABSTRAK Tujuan penelitian ini adalah menguji efektivitas tepung batang pisang ambon dalam pakan terhadap status kesehatan dan kinerja produksi ikan kerapu cantang yang didederkan dalam KJA di laut. Ikan kerapu cantang berukuran 8.27 ± 0.20 cm dengan bobot rata-rata 11.69 ± 0.50 g dipelihara dalam KJA berukuran 1 m × 1 m × 1.5 m (kedalaman air 2,5 m) dengan kepadatan 112 ekor/m2 dan dipelihara selama 42 hari. Pakan yang digunakan adalah pakan komersil dengan protein 46% dan 48%, yang selanjutnya ditambahkan tepung batang pisang ambon sebanyak 30 g/kg pakan dengan metode coating. Penelitian ini menggunakan tiga perlakuan dan tiga ulangan yakni pemberian pakan perlakuan di awal pemeliharaan selama 7 hari (A), 14 hari (B) dan tanpa pemberian pakan dengan tepung batang pisang ambon (kontrol). Parameter yang diamati adalah kinerja produksi, morfometrik, uji hematologi dan pengukuran kualitas air. Hasil penelitian menunjukkan kinerja produksi antar perlakuan tidak berbeda signifikan (P>0.05). Berdasarkan pada uji morfometrik pada bagian panjang total untuk perlakuan A ditemukan peningkatan signifikan (P<0.05) dibandingkan perlakuan kontrol dan B. Pada uji hematologi hari ke-14 diketahui total eritrosit, hemoglobin, hematokrit dan total leukosit tertinggi terdapat pada perlakuan B, sedangkan nilai diferensial leukosit antar perlakuan tidak berbeda signifikan (P>0.05). Penambahan tepung batang pisang ambon dalam pakan pada 14 hari pertama pemeliharaan (B) dapat meningkatkan status kesehatan, namun belum mampu meningkatkan kinerja produksi dan morfometrik ikan kerapu. Kata kunci: ikan kerapu cantang, kinerja produksi, status kesehatan, tepung batang pisang ambon